OntoCS: A Web-Based System for Collaborative Ontology Construction - Hwang, Dosam; Lee, In Keun; Jung, Jason J. (COMPUTING AND INFORMATICS, 2012)
A number of studies on ontology editing tools and ontology-based applications have been proposed for automatically processing knowledge and information. However, the existing methodologies and tools for dealing with ontologies have assumed that the system is restricted to a single user. Main motivation of this paper is to foster collaborations between users, because ontology building is an expensive task. Thereby, in this paper, we present a web-based ontology construction and integration system, which is called OntoCS, to support collaborative interactions between people during creating ontologies. Particularly, inexpert users can collect available language resources from the web to describe concepts in a (even unfamiliar) domain. We believe that this collaborative process is implementing collective intelligence. In conclusion, we have shown that the proposed OntoCS system can efficiently edit and manage multiple ontologies over time.